Immunization of rabbits with synthetic peptides derived from a highly conserved β-sheet epitope region underneath the receptor binding site of influenza A virus - Ideno S (Dove Medical Press, 2013)
Shoji Ideno,1,3 Kaoru Sakai,1 Mikihiro Yunoki,2–4 Ritsuko Kubota-Koketsu,3,5 Yuji Inoue,3 Shota Nakamura,6 Teruo Yasunaga,6 Yoshinobu Okuno,5 Kazuyoshi Ikuta3 1Infectious Pathogen Research Section, Central Research Laboratory, Research and Development Division, Japan Blood Products Organization, Kobe, Japan; 2Research and Development Promotion Section, Research and Development Division, Japan Blood Products Organization, Tokyo, Japan; 3Department of Virology, Research Institute for Microbial Diseases, Osaka University, Suita, Osaka, Japan; 4Department of Veterinary Microbiology, School of Veterinary Medicine, Rakuno Gakuen University, Ebetsu, Hokkaido, Japan; 5Kanonji Institute, The Research Foundation for Microbial Diseases of Osaka University, Kanonji, Kagawa, Japan; 6Department of Genome Informatics, Genome Information Research Center, Research Institute for Microbial Diseases, Osaka University, Suita, Osaka, Japan Background: There is increasing concern about the speed with which health care providers can administer prophylaxis and treatment in an influenza pandemic. Generally, it takes several months to manufacture an influenza vaccine by propagation of the virus in chicken eggs or cultured cells. Newer, faster protocols for the production of vaccines that induce broad-spectrum immunity are therefore highly desirable. We previously developed human monoclonal antibody B-1 that shows broadly neutralizing activity against influenza A virus H3N2. B-1 recognizes an epitope region that includes an antiparallel β-sheet structure underneath the receptor binding site of influenza hemagglutinin (HA). In this study, the efficacy of a synthetic peptide vaccine derived from this epitope region against influenza A was evaluated. Materials and methods: Two peptides were synthesized, the upper and lower peptides. These peptides comprise amino acid residues 167–187 and 225–241, respectively, of the B-1 epitope region of HA, which is involved in forming the β-sheet structure. Both peptides were then coupled to keyhole limpet hemocyanin, and the peptides, alone or in combination, were used to immunize rabbits. The resulting antibody responses were examined by enzyme-linked immunosorbent assay. The upper peptide, but not the lower peptide, elicited antibodies that were reactive to HA. Interestingly, the use of both peptides together could elicit antibodies with a higher reactivity to HA than either peptide alone. The antibodies were found to react to HA at the N-terminus of the upper peptide, which is exposed at the surface of trimeric HA on influenza virions. Discussion: The higher production of HA-reactive antibodies following immunization with both peptides suggests that the upper peptide forms the effective epitope structure in the binding state, and the lower peptide enhances the production of HA antibodies. This study could be the first step towards the development of pandemic viral vaccines that can be produced within short time periods. Keywords: influenza A, hemagglutinin, epitope, synthetic peptide, rabbit